KECEMASAN MENGHADAPI SIDANG SKRIPSI DITINJAU DARI BEHAVIOUR MAHASISWA - Astuti, Livia; Winarti, Agus (Universitas Insan Cendekia Mandiri, 2024)
Abstract:. Anxiety among students when preparing their final assignment/thesis there is a feeling of anxiety that is felt, because they are afraid or worried about the threat of not being able to complete the final assignment. The aim of this research is to find out how severe the anxiety experienced by students is and what behavior occurs in students. The research method used is a descriptive approach with qualitative methods. Data collection techniques through interviews, observation and documentation. The use of this instrument is intended to determine student anxiety in facing the thesis trial in terms of student behavior/attitudes or behavior. The subjects of this research were students who were going to face a thesis exam and who were working on their thesis. The results of the research obtained were that students experienced (a) Realistic anxiety, namely fear of danger from the external world, and the level of anxiety was in accordance with the degree of threat that existed, as many as three people (b ) Moral anxiety is fear of one's own conscience, fear of the punishment that will be received from parents or other authority figures if a person satisfies instincts in his own way, which he believes will result in punishment, as many as five people. (c) There are two types of neurotic anxiety, namely fear of punishment that will be received from parents or other authority figures. If someone satisfies his instincts in his own way, he believes he will reap punishment. The conclusion is that anxiety facing the thesis trial is reviewed from student behavior into three human behaviors: (a) Cognitive; Disturbance of attention, loss of concentration, easy forgetting, misinterpretation, confusion, decreased field of perception, excessive self-awareness, excessive worry, decreased objectivity, fear of accidents, and so on. (c) Affective: impatient, tense, neurosis, tremor, extreme nervousness, very restless and others. (c) psychomotor; Restlessness, tremors, nervousness, rapid speech and lack of coordination, withdrawal and avoidance